Following the money: Evidence for the portfolio balance channel of quantitative easing - Itay Goldstein; Jonathan Witmer; Jing Yang (Bank of Canada, 2018)
Recent research suggests that quantitative easing (QE) may affect a broad range of asset prices through a portfolio balance channel. Using novel security-level holding data of individual US mutual funds, we establish evidence that portfolio rebalancing occurred both within and across funds. Contrary to conventional wisdom, portfolio rebalancing by fund managers into riskier assets is much smaller in magnitude than into other government bonds. We find that mutual funds replaced QE securities with other government bonds that have similar characteristics. Intriguingly, this shift occurred mainly into newly issued government bonds. Such within-fund portfolio rebalancing is material. For every 100 in QE bonds sold, mutual funds replenished their portfolios with about 50 to 60 of newly issued government bonds. Thus, QE played an important role in funding treasury debt issuance during this period. Meanwhile, the rebalancing into riskier assets, such as corporate bonds, did occur, but was mainly carried out by the end investors of the funds instead of the fund managers themselves.
Keywords: E5; E58; G23; 330; Monetary policy; Monetary policy implementation; Transmission of monetary policy